Phacoemulsification versus Phacoemulsification/Trabeculectomy for the Treatment of Primary Open-Angle Glaucoma Coexistent with Cataract: A Comparative Study - Athanasios Kaliardas; Irini Chatziralli; Andreas Katsanos; George Kitsos (Medicina, 2023)
Background: The purpose of this study was to evaluate the clinical outcomes in patients with primary open-angle glaucoma (POAG) and coexistent cataract treated with phacoemulsification cataract surgery, either alone or in combination with trabeculectomy. Methods: Participants in this retrospective study were 52 patients diagnosed with previously controlled POAG and coexistent cataract, who underwent either uneventful phacoemulsification cataract surgery (Group I, n = 27) or combined uneventful phacoemulsification cataract surgery and trabeculectomy (Group II, n = 25), with at least a 24-month postoperative follow-up. We recorded the changes in intraocular pressure (IOP) and in the need of anti-glaucoma medications before and after surgical procedures. Results: There was a statistically significant decrease in IOP at postoperative day 7 in both groups (p < 0.001), which remained until the end of the 24-month follow-up. At month 24, the two groups did not differ significantly in terms of IOP (14.3 ± 1.4 vs. 13.1 ± 1.2 for Group I and Group II, respectively; p = 0.447). In addition, there was a statistically significant decrease in the number of anti-glaucoma medications needed at postoperative day 7 in both groups (p < 0.001 for both groups compared to baseline). At month 24, patients in both groups needed about one additional anti-glaucoma medication to control their IOP. Of note, during the first month after surgery, 20% of patients in Group II needed 0.1 mL 5-FU injections to the bleb, although antimetabolites were not used in the primary surgery. Conclusions: Both surgical interventions, namely phacoemulsification cataract surgery alone and phacoemulsification/trabeculectomy, were found to be effective in the management of POAG with coexistent cataract, presenting a significant decrease in IOP and in the need of anti-glaucoma medications postoperatively at a long-term follow-up period of 24 months.